The Relationship Between Staff Nurses' Advocacy For Patient Safety Behaviors And Safety Management Approaches At Saudi Arabia 2024 (The Review of Diabetic Studies, 2024)
Background: Advocacy is the essence of nursing’s professional commitment to the preservation of human rights, protection of patients from harm, and the provision of quality patient care. Awareness of the vital role advocacy plays in advancing safe clinical practice has grown as a result of the current emphasis on patient safety. It has received a lot of attention how crucial nurses' propensity to speak up in clinical settings is to enhancing patient safety and treatment quality.The study aimed: To examine the relationship between staff nurses' advocacy for patient safety behaviors and safety management approaches at Saudi Arabia, 2024.Methods: A descriptive correlational research design was used among convenience sample of nurses (130). Two tools were used namely: Safety Management Approaches Questionnaire and Advocacy for Patient Safety Behaviors (Speaking Up For Patient Safety) Questionnaire.Results: Regarding control-based safety management, the most important thing to emphasize was the significance of safety rules and regulations. The most important aspect of commitment-based safety management was determined to be raising safety awareness. The one simulated activity (vignette) was determined to have the highest level of support for patient safety practices. About three quarters of the nurses in the survey had a moderate degree of speaking up for patient safety behaviors, according to the study's findings.Conclusion: A statistically significant inverse relationship was found between advocating for patient safety behavior and a control-based safety management approach. In order to monitor patient safety, provide nurses with communication and assertiveness training so they can speak up with confidence and competence, and create avenues for the confidential and anonymous reporting of safety issues, leaders should be encouraged to use two safety management systems in tandem rather than just one.